Remediation Practices and Considerations for Virtual Counseling Programs: An emphasis on due process - Elliot Isom (The Advocate, 2021)
Over the past 6 years, the number of accredited Masters Counseling programs has increased from 6 to 75, a growth rate of 233%. In the new expansion of educational technology, programs have better tools to implement a range of educational experiences alongside frameworks to deliver effective counselor education. Much of the counselor-training process involves gatekeeping to enter the profession. One crucial aspect of gatekeeping is training program’s effectiveness at implementing remediation when needed. This article explores strategies and reflective case studies for remediation practices in virtual environments within a counselor education program. The article places an emphasis on applying remediation while ensuring student due process, a practice that can be applied to any training program in a higher education environment.
Keywords: Counselor Training; Gatekeeping; Remediation; Virtual Education